Complexin inhibits spontaneous release and synchronizes Ca2+-triggered synaptic vesicle fusion by distinct mechanisms - Lai, Ying; Diao, Jiajie; Cipriano, Daniel J; Zhang, Yunxiang; Pfuetzner, Richard A; Padolina, Mark S; Brunger, Axel T (eLife, 2014)
Previously we showed that fast Ca2+-triggered vesicle fusion with reconstituted neuronal SNAREs and synaptotagmin-1 begins from an initial hemifusion-free membrane point contact, rather than a hemifusion diaphragm, using a single vesicle–vesicle lipid/content mixing assay (Diao et al., 2012). When complexin-1 was included, a more pronounced Ca2+-triggered fusion burst was observed, effectively synchronizing the process. Here we show that complexin-1 also reduces spontaneous fusion in the same assay. Moreover, distinct effects of several complexin-1 truncation mutants on spontaneous and Ca2+-triggered fusion closely mimic those observed in neuronal cultures. The very N-terminal domain is essential for synchronization of Ca2+-triggered fusion, but not for suppression of spontaneous fusion, whereas the opposite is true for the C-terminal domain. By systematically varying the complexin-1 concentration, we observed differences in titration behavior for spontaneous and Ca2+-triggered fusion. Taken together, complexin-1 utilizes distinct mechanisms for synchronization of Ca2+-triggered fusion and inhibition of spontaneous fusion.
Keywords: synaptic vesicle fusion; neurotransmitter release; complexin; synaptotagmin; SNARE; membrane fusion